Terrorism in the name of Islam: Bangladesh perspective - Siddika, Ayesha (Philosophy and Progress, 2021)
This research aims at exploring various factors of terrorism in the name of Islam in Bangladesh with a special preference to understand the causal relation between religion and terrorism. Bangladesh has been suffering from the crisis of religious militancy for the last couple of decades. Terrorist activities such as bombing, murder, burning houses, destructing temples and house of people belonging to other religions induced fear among the people of Bangladesh. Terrorists have been using the name of Islam as a safeguard of their heinous activities. This study argues that there is no connection between terrorism and Islam. This research finds that the lack of knowledge of the religion of Islam as well as other religions, unemployment, social media, global rise of militancy in the name of Islam and different psychological issues work behind terrorism in the name of Islam in Bangladesh. In the face of a global rise of religious militancy or militancy in the name of Islam, it requires a comprehensive study on terrorism in the name of Islam from the perspectives of Bangladesh. Philosophy and Progress, Vol#63-64-; No#1-2; Jan-Dec 2018 P 109-124